Improving The Business Environment in East Java : Views From The Private Sector - World Bank; Asia Foundation (Jakarta: World Bank and Asia Foundation, 2012)
This report presents the results of research undertaken by The World Bank and The Asia Foundation to identify barriers to trade and investment in East Java. This activity was initiated by the World Bank and The Asia Foundation with several important aims: (i) to support private sector participation in the public planning process related to potential World Bank assistance for infrastructure projects; (ii) to provide an opportunity for the private sector to express their concerns to local governments and to make recommendations for improving the business climate; and (iii) to encourage increased coordination between local governments in stimulating trade between regions. The role of the Asia Foundation / World Bank Team was to identify barriers to trade and investment and to facilitate activities to introduce a sustainable and replicable process for how regional governments can best work with the private sector in creating a conducive business climate.